Self Confidence, Adversity Quotient, Mathematics Problem-Solving Ability, Elementary School Students, Mathematics Education, Educational Psychology - Alfian, Denis; Pramono, Suwito Eko; Isnaeni, Wiwi (Universitas Negeri Semarang, 2025)
. Mathematics problem-solving ability is a fundamental skill in elementary education that is influenced by various psychological factors. This study aims to investigate the effects of self-confidence and adversity quotient on the problem-solving skills of fifth-grade students at SD Negeri Arjawinangun. Using a quantitative correlational design, the study involved a total sample of 100 students. Data were collected through validated and reliable questionnaires measuring self-confidence and adversity quotient, along with a mathematics problem-solving test. Prior to analysis, assumptions of normality, linearity, and multicollinearity were confirmed. Multiple linear regression analysis revealed that both self-confidence and adversity quotient had a significant positive effect on students’ problem-solving abilities, with regression coefficients of 0.45 and 0.37 respectively (p < 0.05). The regression model accounted for 62% of the variance in problem-solving ability. These findings highlight the crucial role of psychological resilience and confidence in enhancing mathematical problem-solving at the elementary level. However, given the correlational design, causal inferences cannot be definitively made. The results suggest that educators should focus on fostering students’ psychological strengths alongside cognitive skills to improve academic outcomes. Future research is recommended to employ experimental designs and incorporate additional variables to deepen understanding of the factors influencing mathematical problem-solving